2021
DOI: 10.1108/ijcst-02-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Tolerable range of abdomen and waist skin temperature for heating-capable smart garments

Abstract: Purpose This study aims to provide information on how to monitor the temperature setting of a heating device in order to implement a heating unit successfully in the smart clothing by observing voluntary heating behavior of wearers.Design/methodology/approach Subjects wearing base layers and additional clothing were asked to turn on and off the switch when wanted in the cold environmental chamber. Tolerable range of skin temperature (TST) depending on the location of body was obtained by observing the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A preliminary review of the literature has been carried out into trials seeking to evaluate the efficacy of heating e-textiles in cold environments. [4][5][6][7][8][9][10][14][15][16][17][18] Relevant keywords related to heating, textile, and cold environments were identified and preliminary results showed that the common body regions heated by thermal e-textiles are: (a) torso, (b) feet/toes, and (c) more than two regions. To examine thermal wear performance, researchers generally had an experimental group (HEAT) placed in a cold environment and a control group (CON) situated in a thermo-neutral or in a cold environment but wearing unheated clothing.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A preliminary review of the literature has been carried out into trials seeking to evaluate the efficacy of heating e-textiles in cold environments. [4][5][6][7][8][9][10][14][15][16][17][18] Relevant keywords related to heating, textile, and cold environments were identified and preliminary results showed that the common body regions heated by thermal e-textiles are: (a) torso, (b) feet/toes, and (c) more than two regions. To examine thermal wear performance, researchers generally had an experimental group (HEAT) placed in a cold environment and a control group (CON) situated in a thermo-neutral or in a cold environment but wearing unheated clothing.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of TS and CS, the subjective evaluation would often be assessed by perception ratings from the responders. 4,[7][8][9][10]15,16 Age group, gender, thermal sensitivity, and the type of heating e-textile, i.e. different body region being heated, may be considered as moderators.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations